Barnyard Millet for Food and Nutritional Security: Current Status and Future Research Direction - Renganathan, Vellaichamy Gandhimeyyan; Vanniarajan, Chockalingam; Karthikeyan, Adhimoolam; Ramalingam, Jegadeesan (Frontiers in Genetics, 2020)
Barnyard millet (Echinochloa species) has become one of the important minor millet crops in Asia, showing a firm upsurge in world production. The genus Echinochloa comprises two major species E. esculenta and E. frumentacea, which are predominantly cultivated for human consumption and livestock feed. They are less susceptible to biotic and abiotic stresses. Barnyard millet grain is a good source of protein, carbohydrate, fibre and contains most notably micronutrients (iron and zinc) compared to major cereals. Despite its nutritional and agronomic benefits, barnyard millet has remained as an underutilized crop. Over the past decades, very limited attempts have been made to study the features of this crop. Hence, more concerted research efforts are required to characterize germplasm resources, identify trait-specific donors, develop mapping population and discover QTL/gene (s). The recent release of genome and transcriptome sequences of wild and cultivated Echinochloa species, respectively has facilitated in understanding the genetic architecture and decoding the rapport between genotype and phenotype of micronutrients and agronomic traits in this crop. In this review, we highlight the importance of barnyard millet in the current scenario and discuss the up-to-date status of genetic and genomics research and the research gaps to be worked upon by suggesting directions for future research to make barnyard millet a potential crop in contributing to food and nutritional security.